Guia didático para o ensino de biologia: explorando etapas do caminho do oxigênio, da fotossíntese à respiração celular. - Torri, Renata Carrara (2025)
The teaching of biochemical concepts, such as photosynthesis and cellular respiration, represents a challenge in high school, as it involves complex processes that require an understanding of phenomena at the molecular level. This difficulty was evidenced by the results of the Espírito Santo Basic Education Assessment Program (PAEBES) 2023, which indicated that more than half of the students showed insufficient performance in Biology, especially in content related to these processes. In this context, this study aimed to develop and validate a Teaching Guide with a practical and investigative approach that addresses stages of the oxygen pathway, from its release during photosynthesis to its use in respiration. The teaching guide was structured with activities based on active methodologies such as experimentation, simulations, and dramatizations, aiming to promote meaningful learning and student protagonism. The proposal was applied to a class of 25 full-time high school students and was evaluated using qualitative and quantitative methods through questionnaires, responses to lesson scripts, and observations by the teacher-researcher. The results suggest relevant conceptual advances, such as conceptual restructuring, greater clarity in the understanding of biochemical processes, and, most importantly, recognition of the pathway of oxygen from its release in photosynthesis to its utilization in cells. Students also highlighted the motivation, dynamism, and participation provided by the activities, demonstrating engagement and active involvement in the learning process. This study indicates that the teaching guide can contribute to the consolidation of fundamental biochemical concepts and serves as a practical, flexible, and adaptable instructional resource for the realities of public schools.